Inpatient treatment of patients with acute idiopathic peripheral facial palsy: A population‐based healthcare research study. (2nd April 2017) - Plumbaum, K.; Volk, G.F.; Boeger, D.; Buentzel, J.; Esser, D.; Steinbrecher, A.; Hoffmann, K.; Jecker, P.; Mueller, A.; Radtke, G.; Witte, O.W.; Guntinas‐Lichius, O.
Abstract: Objectives: To determine the inpatient management for patients with acute idiopathic facial palsy (IFP) in Thuringia, Germany. Design: Population‐based study. Setting: All inpatients with IFP in all hospitals with departments of otolaryngology and neurology in 2012, in the German federal state, Thuringia. Main outcome measures: Patients' characteristics and treatment were compared between departments, and the probability of recovery was tested. Results: A total of 291 patients were mainly treated in departments of otolaryngology (55%) and neurology (36%). Corticosteroid treatment was the predominant therapy (84.5%). The probability to receive a facial nerve grading (odds ratio [OR=12.939; 95% confidence interval [CI]=3.599 to 46.516), gustatory testing (OR=6.878; CI=1.064 to 44.474) and audiometry (OR=32.505; CI=1.485 to 711.257) was significantly higher in otolaryngology departments, but lower for cranial CT (OR=0.192; CI=0.061 to 0.602), cerebrospinal fluid examination (OR=0.024; CI=0.006 to 0.102). A total of 131 patients (45%) showed a recovery to House‐Brackmann grade≤II. A pathological stapedial reflex test (Hazard ratio [HR]=0.416; CI=0.180 to 0.959) was the only independent diagnostic predictor of worse outcome. Prednisolone dose >500 mg (HR=0.579; CI 0.400 to 0.838) and no adjuvant physiotherapy (HR=0.568; CI=0.407 to 0.794) were treatment‐related predictors of worse outcome. Conclusions: Inpatient treatment of IFP seems to be highly variable in daily practice, partly depending on the treating discipline and despite the availability of evidence‐based guidelines. The population‐based recovery rate was worse than reported in clinical trials.